2021
DOI: 10.3390/ijerph18041750
|View full text |Cite
|
Sign up to set email alerts
|

How Dentists Face the COVID-19 in Mexico: A Nationwide Cross-Sectional Study

Abstract: Background: on 7 January 2020, a new type of coronavirus was isolated, the Severe Acute Respiratory Syndrome Coronavirus2 (SARS-CoV-2), the organism causing the outbreak that has affected the lives of all humans and has modified the rules of coexistence around the world. In Mexico, from 3 January 2020 to 9 January 2021, there have been 1439, 569 confirmed cases of COVID-19 with 131,031 deaths. The World Health Organization reported that Mexico was ranked twelfth, in terms of confirmed cases of COVID-19 by coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
3
7
0
2
Order By: Relevance
“…Our study was carried out in March – April 2021, and the early provision of resources and guidance by the ADA could explain why most respondents had 'good to very good’ knowledge of COVID-19. This finding is consistent with international studies 9 , 15 , 35 , 36 , 37 , 38 , where it has been reported that dentists have a good command of COVID-19 knowledge. Only one study from Pakistan has reported insufficient knowledge among dentists, particularly regarding fundamental COVID-19 disinfection protocols, despite available guidelines.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study was carried out in March – April 2021, and the early provision of resources and guidance by the ADA could explain why most respondents had 'good to very good’ knowledge of COVID-19. This finding is consistent with international studies 9 , 15 , 35 , 36 , 37 , 38 , where it has been reported that dentists have a good command of COVID-19 knowledge. Only one study from Pakistan has reported insufficient knowledge among dentists, particularly regarding fundamental COVID-19 disinfection protocols, despite available guidelines.…”
Section: Discussionsupporting
confidence: 92%
“… 13 Such measures have included triage and screening of patients for COVID-19, additional infection prevention and control measures, and use of personal protective equipment (PPE). 14 , 15 , 16 , 17…”
Section: Introductionmentioning
confidence: 99%
“…Like other frontline healthcare workers, a major challenge faced by dentists was having to adjust their services and workflows to ensure patient safety and minimise risk of transmission [ [9] , [10] , [11] ]. They have introduced various enhanced infection prevention and control (IPC) practices to their workplaces, including triage/screening of patients for COVID-19, regular disinfection of equipment and surfaces, performing hand hygiene, and use of personal protective equipment [ [12] , [13] , [14] , [15] ]. Studies have reported anxiety amongst dentists regarding the risks of contracting SARS-CoV-2 and passing the infection to household members [ 9 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that only 12.3% of participants could obtain personal protective equipment (PPE) including FFP2 masks, and dentists registered important economic losses due to the interruption of their activity. Casillas Santana et al [ 6 ] showed that only a small percentage of Mexican dentists used protective masks and a large majority had to change disinfection rules between appointments to ensure a safe environment for patients. Consolo et al [ 7 ] found that dentists from northern Italy reported feelings of concern (70.2%), anxiety (46.4%) and fear (42.4%) and most of them (89.6%) mentioned increased concerns about their professional future.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the coronavirus-19 pandemic, the impact on mental health is just at the beginning. Studies have identified the influence of the pandemic on the psychological, physical, social, and financial status as an acute reaction [ 6 , 8 , 14 ].…”
Section: Introductionmentioning
confidence: 99%